Using Contingency Contracting to Promote Social Interactions Among Students With ASD and Their Peers. Issue 5 (September 2021) - Alwahbi, Abdullah; Hua, Youjia
The purpose of this study was to evaluate the effect of peer training implemented alone and the effect of combining contingency contracting with peer training on promoting social interactions among students with ASD and their peers. Three students with ASD and six typically developing peers enrolled in an inclusive elementary school participated in the study. Ten-minute observations were conducted during recess time to collect data on the participants' social interactions. The data obtained showed that peer training alone did not result in improvement in social interactions. However, upon the introduction of contingency contracting, which facilitated the use of prompting and reinforcement, the participants engaged in a significantly higher number of social interactions. The findings about the effect of peer training and contingency contracting were consistent across the participants. The study results suggest several implications for practice and directions for future research.